2016
DOI: 10.1159/000447745
|View full text |Cite
|
Sign up to set email alerts
|

Y-27632, a Rho-Associated Protein Kinase Inhibitor, Inhibits Voltage-Dependent K+ Channels in Rabbit Coronary Arterial Smooth Muscle Cells

Abstract: We examined the effects of the Rho-associated protein kinase (ROCK) inhibitor Y-27632 on voltage-dependent K+ (Kv) channels in rabbit coronary arterial smooth muscle cells using the whole-cell patch clamp technique. Y-27632 reduced the amplitude of the Kv current in a concentration-dependent manner, with an IC50 of 0.87 ± 0.06 μmol/l and a Hill coefficient of 1.48 ± 0.06. Y-27632 did not affect the steady-state activation or inactivation curves, suggesting that the drug does not affect th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…To date, several research groups, including ours, have demonstrated the side effects of various drugs or chemicals on Kv channels, irrespective of their own function. For example, several protein kinase modulators, such as LY 294002 (a PI3 kinase inhibitor), H‐89 (a protein kinase A inhibitor), genistein (a tyrosine kinase inhibitor), bisindolylmaleimide (I) (a protein kinase C inhibitor), YC‐1 (a guanylyl cyclase activator), and Y‐27632 (a Rho‐associated protein kinase inhibitor), have been shown to inhibit vascular Kv channels without affecting their own function . In addition, Ca 2+ channel inhibitors, including verapamil, mibefradil, efonidipine, and NNC 55‐0396, directly inhibit vascular Kv channels independent of Ca 2+ channel inhibition .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, several research groups, including ours, have demonstrated the side effects of various drugs or chemicals on Kv channels, irrespective of their own function. For example, several protein kinase modulators, such as LY 294002 (a PI3 kinase inhibitor), H‐89 (a protein kinase A inhibitor), genistein (a tyrosine kinase inhibitor), bisindolylmaleimide (I) (a protein kinase C inhibitor), YC‐1 (a guanylyl cyclase activator), and Y‐27632 (a Rho‐associated protein kinase inhibitor), have been shown to inhibit vascular Kv channels without affecting their own function . In addition, Ca 2+ channel inhibitors, including verapamil, mibefradil, efonidipine, and NNC 55‐0396, directly inhibit vascular Kv channels independent of Ca 2+ channel inhibition .…”
Section: Discussionmentioning
confidence: 99%
“…5 have been shown to inhibit vascular Kv channels without affecting their own function. 11,[16][17][18][19][20] In addition, Ca 2+ channel inhibitors, including verapamil, mibefradil, efonidipine, and NNC 55-0396, directly inhibit vascular Kv channels independent of Ca 2+ channel inhibition. [21][22][23][24] Calmodulin inhibitors, such as trifluoperazine, W-7, and CGS 9343B, have also been reported to inhibit the vascular Kv current irrespective of calmodulin inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…Y-27632 was originally disclosed as a calcium blocker (Muro et al, 1990) and reported to be active as relaxant of vascular and bronchial smooth muscles (Uehata, 1997). Although largely utilized as T pharmacological tool, Y-27632 shows moderate potency on ROCK and poor selectivity (Ishizaki et al, 2000) and inhibits voltage-dependent potassium channels in arterial smooth muscle cells (Li et al, 2016). Despite their large use, both fasudil and Y-27632 are limited by poor selectivity and low on-target potency resulting in non-specific pharmacological and toxic effects (Li et al, 2016;Asano et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Fukushima et al (2005) reported that fasudil suppresses the collagen secretion and increased the collagenase activity in hepatic stellate cells suggesting its contribution to the cervical action showes relaxant effect on vascular and myometrial smooth muscle (Shimomura et al, 2004). Li et al (2016) found that Y-27632 inhibits the voltage dependent potassium (Kv) channels and reduces the muscle tone in vascular smooth muscle. This ability might be associated with the cervical resistance decreasing effect of the drug, because Kv channel expressions have been confirmed in smooth muscle part of cervix (de Lera Ruiz and Kraus, 2015).…”
mentioning
confidence: 99%